In vitro Evaluation of Antioxidant properties of Hodgsonia heteroclita (Cucurbitaceae) fruit - Silu Basumatary, Ajit Kumar Das, Raaman Nanjian, Gauri Dutt Sharma (Journal of Applied Pharmaceutical Science, 2015)
Hodgsonia heteroclita fruits have been used as traditional drug for antidiabetic in Western Assam, India. The study aimed to investigate antioxidant activity of methanolic fruit extract of H. heteroclita. The antioxidant activity of fruit was determined by employing different In vitro assays such as DPPH•, ABTS•+ radical scavenging capacities and reducing power assay-phosphomolybdenum. The results of the present study revealed that the methanol fruit extract exhibited strong scavenging effect on DPPH (2,2-diphenyl-1picrylhydrazyl) with IC50 =20.98±0.17 than ABTS [2,2´-azino-bis(3-ethylbenzothiazoline-6-sulphonate) with IC50 =28.58±0.42. The reducing power phosphomolybdenum assay showed inhibition with ascorbic acid as standard. Fruit extract exhibit free radical scavenging and reducing properties which might constitute an important source of natural antioxidants. Thus the study indicates that this plant has a potential to be used as an antioxidant and also can be used to prevent diseases directly linked to oxidative stress.
Keywords: Hodgsonia heteroclita,antioxidant activity,DPPH,ABTS and phosphomolybdenum.